Choreographing the Airport Field Notes from the Transit Spaces of Global Mobility - Shih Pearson, Justine (Springer International Publishing, 2018)
This book investigates the global hub airport as an exemplar of cosmopolitan culture and space. A machine made for movement, itself perched at the crossroads of the world's incessant mobility, the airport is both a symbol of and stage for the ways in which we construct and inhabit the world today. Taking an ethnographically-inflected approach, this study brings together knowledge of the moving body from dance and performance and the study of systems of mobility within cultural and mobilities studies, in order to call attention to the kinaesthetic experience of global space. What is the choreography of the global airport? How does it perform on us. How do we perform within it? Extending thinking about contemporary cosmopolitanism and cultural identity, and the performativity of places and identities, this book is essential reading for those interested in cultural debates around globalisation, the innovative application of performance theory towards everyday experience, and interdisciplinary methodologies.